Total Edge Irregularity Strength of Star Snake Graphs (European Journal of Pure and Applied Mathematics, 2025)
In different fields in our life, like physics, coding theory and computer science, graph labeling dramas an vital role and appears in many applications. A labeling of a graph  is a map which assign each element in  with a positive integer number. An edge irregular total   -labeling is a function  such that   where  and  are weights for any two distinct edges. In this case,     has total edge irregularity strength  (TEIS) if  is minimum. In our paper, we defined a new type of graphs called a triple star snake graph and star snake graph . Also, we investigated TEIS for a triple star snake graph  . After that, we generalized the results for star snake graph .
Keywords: Edge labeling; Irregularity strength; Irregular labelling; Total edge irregularity strength; Star snake graph.